Risk Factors for Epilepsy After Thrombolysis for Ischemic Stroke: A Cohort Study - Brondani, Rosane; de Almeida, Andrea Garcia; Cherubini, Pedro Abrahim; Secchi, Thaís Leite; de Oliveira, Marina Amaral; Martins, Sheila Cristina Ouriques; Bianchin, Marino Muxfeldt (Frontiers in Neurology, 2020)
The effects of thrombolysis in seizure and epilepsy after acute ischemic stroke have been poorly explored. In this study, we examine risk factors and consequences of intravenous rt-PA for treatment of acute ischemic stroke. In a retrospective cohort study we evaluate risk factors for seizure and epilepsy after stroke thrombolysis, as well as the impact of seizures and epilepsy in outcome of stroke patients. In our cohort, mean age of patients was 67.2 years old (SD = 13.1) and 79 of them (51.6%) were male and. Initial NIHSS mean score were 10.95 (SD = 6.25). Three months NIHSS mean score was 2.09 (SD = 3.55). Eighty seven (56.9%) patients were mRS of 0–1 after thrombolysis. Hemorrhagic transformation was observed in 22 (14.4%) patients. Twenty-one (13.7%) patients had seizures and 15 (9.8%) patients developed epilepsy after thrombolysis. Seizures were independently associated with hemorrhagic transformation (OR = 3.26; 95% CI = 1.08–9.78; p = 0.035) and with mRS ≥ 2 at 3 months after stroke (OR = 3.51; 95% CI = 1.20–10.32; p = 0.022). Hemorrhagic transformation (OR = 3.55; 95% CI = 1.11–11.34; p = 0.033) and mRS ≥ 2 at 3 months (OR = 5.82; 95% CI = 1.45–23.42; p = 0.013) were variables independently associated with post-stroke epilepsy. In our study, independent risks factors for poor outcome in stroke thrombolysis were age (OR = 1.03; 95% CI = 1.01–1.06; p = 0.011), higher NIHSS (OR = 1.08; 95% CI = 1.03–1.14; p = 0.001), hemorrhagic transformation (OR = 2.33; 95% CI = 1.11–4.76; p = 0.024), seizures (OR = 3.07; 95% CI = 1.22–7.75; p = 0.018) and large cortical area (ASPECTS ≤ 7) (OR = 2.04; 95% CI = 1.04–3.84; p = 0.036). Concluding, in this retrospective cohort study, the neurological impairment after thrombolysis (but not before) and hemorrhagic transformation remained independent risk factors for seizures or post-stroke epilepsy after thrombolysis. Moreover, we observed that seizures emerged as an independent risk factor for poor outcome after thrombolysis therapy in stroke patients (OR = 3.07; 95% CI = 1.22–7.75; p = 0.018).